O09 The impact of an HPV vaccination programme in young men who have sex with men (MSM) on clinical presentations with genital warts. (8th June 2017) - Coleman, Harry; O'Farrell, Nigel; Kapembwa, Moses; Brook, Gary; McSorley, John
Abstract : Introduction: We introduced a quadrivalent HPV (HPV4) vaccination programme in young MSM <27yrs attending our clinical services (Clinic 1 & 2) since 2012. We assess the impact on attendance with genital warts (GW) subsequent to vaccination in this population and an adjoining service (Clinic 3) not then offering vaccination. Methods: We identified all MSM <27yrs receiving at least one dose HPV4 at Clinics 1 & 2, and all MSM <27yrs attending Clinic 3, between 2012 and 2017. Demographic and clinical data was extracted from electronic patient records. HPV DNA testing was not performed. Results: Current or prior history of GW was comparable in the 2 clinic populations. Re-attendance rates were lower in the clinic without active recall. Recurrent episodes of GW was higher 22/180 (12%) in the unvaccinated population than the vaccinated group 11/757 (1.5%). Incidence of new cases of GW, defined as a first clinical episode > 3 months since 1 st vaccine, was significantly lower in the vaccinated population. Discussion: We observed a significant reduction in subsequent episodes and potential new episodes of GW in an unselected population of MSM receiving HPV4 vaccine. Significant clinical benefit and saving can be expected from an HPV4 programme in MSM.